Analisis Penggunaan Lengkung Durasi Aliran (Flow Duration Curve) Untuk Mengetahui Debit Andalan di Sungai Sidoan Kabupaten Parigi Moutong - Oktavia, S.R.; Hidayat, N.; Marampa, M.M. (REKONSTRUKSI TADULAKO: Civil Engineering Journal on Research and Development, 2025)
Limited hydrological information in the form of discharge data on a river or watershed can hinder the process of developing water resources in the area. Based on discharge data recorded at the Sidoan Weir, site in Parigi Moutong Regency, the river has the potential to be used for various purposes, such as irrigation, micro-hydro power plants, raw water, and thus. This study aims to determine the similarity between measured discharge data and calculated discharge data on the Sidoan River, as well as to determine the reliable discharge on the Sidoan River. The data used in this study are climatological data, rainfall data, and discharge data (2011-2020), including a map of the Sidoan watershed. Evapotranspiration analysis was performed using the Modified Penman Method. Measured discharge data was used to determine the similarity with calculated discharge, which was analyzed using the F.J. Mock Method. The Flow Duration Curve (FDC) method was used to analyze the amount of reliable discharge. The results of the study show that the average evapotranspiration value ranges from 100 to 150 mm/month. The parameters used in the water availability analysis with the F.J. Mock method were watershed parameters optimized with a correlation coefficient between measured and calculated discharge of 0.78. The results of the study show that the RMSE values before and after optimization of the watershed parameters are 4.16 and 2.76, respectively. The calculation validation was performed using Mean Absolute Error (MAE). The FDC results show that the 80% - 90% reliable discharge is 0.251 m3/second - 0.150 m3/second, while the 50% reliable discharge is 0.860 m3/second. These results can provide an overview of water availability that can be used for water resource development and management